Learning Dynamics Analysis Based on Computer-Human Interaction - Yang, Sheng; Guo, Lei; Yu, Wensen; Liu, Changyong; Meng, Shimin (International Journal of Emerging Technologies in Learning (iJET), 2013)
Unlike doctors, teachers are not able to carry out personality analysis and teaching diagnosis via using various tools and data. So how can we build the exact teaching environment, collect the data of study process, and perform the evidence-based teaching? To answer the question, computers are introduced to observe study activities, which will surely become an important trend just as in other fields. By designing the cognition process oriented novel study observation software system based on Computer-Human Interaction (CHI) to realize the online observation of study process, massive amount of information that can hardly be obtained by traditional education and psychology is able to be efficiently collected. According to dynamics, data of study process was analyzed to obtain the variables of cognitive dynamics such as study speed, acceleration, average speed, key points, learning kinetic energy and so on. All these parameters reflected the personalities of the learners, which will provide useful information for teaching, training and diagnosis.